Práticas culturais afro-brasileiras na festa de São Benedito em Cuiabá : 2020-2023 - Castrillon, Maria de Lourdes Fanaia (2024)
ABSTRACT: This thesis is part of the Contemporary Poetics research line of the Cultural Studies Program (ECCO) at the Federal University of MT and comprises reflections on “Afro-Brazilian cultural practices of the São Benedito de Cuiabá festival between the years 2020/2023” . And understanding that human practices and their manifestations, such as knowledge, customs, beliefs, values, arts, can be analyzed as symbolic representations. Culture is not determined by the economic structure, but by the creative process of man that escapes social controls and regulations. The historiography of Mato Grosso presents several researches on the celebration of São Benedito, but in this approach the main focus is Afro-Brazilian culture in the saint's festival. To this end, the general objective of the research is to highlight Afro-Brazilian culture in the celebration of São Benedito in Cuiabá, the ways of being and expressing identities of Afro-descendants who for centuries remained on the margins of the historical process, and for this the subjects who build culture Mato Grosso gain relevance in this qualitative scientific writing. In this way I identify: In the face of so many exclusionary and racist strategies and power relations, how did Afro-Brazilian culture survive? How do different subjects with different cultural practices experience the celebration of the black saint that takes place around the Rosário church and São Benedito chapel? What does the resumption of space demarcation involve? What are the power structures involved? On the one hand the ecclesiastical structure and on the other the cultural practice of the Afro-Brazilian group. Other objectives include: Pointing out an overview of the city and the construction of Afro-Brazilian cultural practices spread throughout the city coexisting with other cultures, a process of hybridization. Highlight the construction of devotion to the black saint, the various changes that occurred on the feast of São Benedito, and power relations. It is also important to highlight Congo dance and Capoeira, these are performances that are not always seen as a culture or a relevant art in Mato Grosso society. Nowadays, dances still remain outside the learning process that can be shared as cultural knowledge in the social environment. Another objective is to highlight the Washing of the Stairs of the Igreja do Rosário and chapel of São Benedito de Cuiabá, which emerged in 2017, is a cultural event capable of provoking questions in the social imagination, it is a performance included in the traditional celebration of São Benedito. The methodology used was diverse and included research: documentary, bibliographic, iconographic, media news, open interviews and field research with photographic records and philomatics in all festive and religious celebrations. It is considered that the different aspects of Afro-Brazilian culture and its rituals expressed in the feast of the saint can be valued through research, when brought to the light of knowledge together with the protagonists of the Afro-Brazilian social group, actors of their identities. It is above all a cultural history.